Perancangan Sistem Informasi Pada Pemerintahan Desa Padurenan Berbasis Web Menggunakan Metode Incremental - Erfina Yuanita; Andrian; Syukron Al Azhar; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Padurenan Village is one of the villages in Gunung Sindur District, Bogor Regency. Based on the survey, information was obtained that it was difficult to get information and public services in real time, because the information was recorded manually through letters and announcements directly from the Village Office. This resulted in the difficulty for residents in Padurenan Village to get information and public services in real time because they were constrained by the remote location of the Village Office, and the Village Office which only operated during working hours. Based on these problems, the purpose of this paper is to develop a system to support the services of the Padurenan Village Government and make it easier for the people of Padurenan Village to obtain information and public services. This information system was developed using the incremental method, website-based using the PHP programming language and using the Mysql database. Based on research and development of the Padurenan Village information system this can make it easier to get news information, Village developments and Village activities. The Web-Based Village Information System is capable of recording population data, displaying population data.